A 0.7 GHz and 0.9 GHz efficient and compact dual-band rectifier for ambient radio frequency energy harvesting - Nor Azrin Raja Yunus, Raja; Adam, Ismahayati; Najib Mohd Yasin, Mohd; Muhammad, Surajo; Zuki Azman Wan Muhamad, Wan; Amin Ahmed Ghaleb, Abdulrahman (Institute of Advanced Engineering and Science, 2025)
This study introduces a compact dual-band rectifier utilizing a single and multi-stub matching network (MN) technique. The rectifier consists of two branches, each incorporating a single block stub and two blocks stub to generate two frequency susceptance blocks, subsequently transformed into a meandered line. The proposed rectifier operates at two frequency bands of 0.7 GHz and 0.9 GHz and is fabricated on an RT/Duroid 5880 printed circuit board (PCB) with dimensions of 37×25×1.6 mm using an entire ground architecture. Simulation and measurement results show that the rectifier has a power conversion efficiency (PCE) of 67.77% and 66.35% at 0.7 GHz and 70.31% and 71.22% at 0.9 GHz with input power of 0 dBm, respectively. The rectified voltage is 1.79 V DC across a 5 kΩ load terminal (RL) with 5 dBm input power and is capable of sensing low input power down to -30 dBm. This feature makes the rectifier a promising solution for powering low-power devices from ambient energy.